Evaluating mobile health technologies: does the traditional randomized controlled trial serve our needs?. (16th July 2021) - Gallagher, Robyn; Zhang, Ling
Abstract: Mobile health technologies are increasingly used by cardiovascular nurses and allied health clinicians to support behaviour change and self-care in patients. Randomized controlled trials provide rigorous methodology for evaluation but progress slowly, so the technology is often outdated by completion. A helpful modification to the trial design includes identification of the behaviour intervention principles involved and concurrently track in-app usage data, allowing updates to be made. These data collected alongside user experiences enables analysis of effects on outcomes and determination of the relative influence of component parts. Cardiovascular and mental health mHealth strategies are used to exemplify these recommendations.